El metabolismo social de la comunalidad reconfigurada en Milpa Alta - Carmona Motolinia, José Ramón; Tetreault, Darcy (Pontificia Universidad Católica del Perú, 2023)
Based on an analysis of the struggles of the Nahua peoples of Milpa Alta in Mexico City, this article addresses the following question: How has it been possible to conserve large extensions of forest and agricultural land in a demarcation that is part of one of the largest cities in the world, in rapid expansion since the middle of the last century? The explanation articulates two key categories: reconfigured communality in Milpa Alta through historical struggles that continue to unfold to date; and the social metabolism of human-nature exchanges mediated by the work of various agencies, whose projects come into conflict at different times. We argue that the re-creation of indigenous forms of organization and collective practices have made it possible to curb the extraction of raw materials (wood and water) and land-use change for development projects promoted by government agencies and private companies; in addition to contributing to the conservation of small-scale agricultural practices. The analysis is based on semi-structured interviews that were carried out between 2016 and 2020 with inhabitants of Milpa Alta and on a systematic review of bibliographic, newspaper, statistical, and online sources.

Con base en un análisis de las luchas de los pueblos originarios nahuas de Milpa Alta en la Ciudad de México, este artículo aborda la siguiente pregunta: ¿Cómo ha sido posible conservar grandes extensiones de bosque y tierras agrícolas en una demarcación que forma parte de una de las ciudades más grandes del mundo, en rápida expansión desde mediados del siglo pasado? La explicación articula dos categorías clave: la comunalidad reconfigurada en Milpa Alta por medio de luchas históricas que siguen desenvolviéndose hasta la fecha; y el metabolismo social de los intercambios humano-naturaleza mediados por el trabajo de diversas agencias, cuyos proyectos entran en conflicto en distintos momentos. Argumentamos que la recreación de formas de organización y prácticas colectivas indígenas han permitido frenar la extracción de materias primas (madera y agua) y el cambio de uso de suelo para proyectos de desarrollo impulsados por agencias gubernamentales y compañías privadas; además de contribuir a la conservación de prácticas agrícolas de escala pequeña. El análisis se basa en entrevistas semiestructuradas que se realizaron entre 2016 y 2020 con habitantes de Milpa Alta y en una revisión sistemática de fuentes bibliográficas, hemerográficas, estadísticas y documentos en línea.
The Social Metabolism of Reconfigured Communality in Milpa Alta
Keywords: Reconfigured communality; Social metabolism; Indigenous peoples; Milpa Alta; Ciudad de México; Comunalidad reconfigurada; Metabolismo social; Pueblos originarios; Milpa Alta; Ciudad de México; https://purl.org/pe-repo/ocde/ford#5.04.00